Mathematical model of dynamic motion nutrient solution in an electrostatic field - Inozemtsev, G.; Schylcov, A.; Vaschyshyn, S. (Енергетика і автоматика, 2015)
The mathematical model of the dynamics of nutrient solution in an electrostatic field that makes possible the definition of process parameters for the application of electro-technological complex nutrient solutions for plants.